Motivation Of Parents In Involving Their Children In Basketball Club - Prasetya, Muhammad Reza Aziz; Wismanadi, Himawan (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2024)
Sport has certainly become an activity that humans need in today's era, because regular exercise keeps the body healthy and fit, rather than not doing sports activities, every parent's motivation for their child must be different and varied, but all of them are positive things for a child's development, Of course, motivation for children is very necessary. This study aims to analyze the motivation of parents to their children in increasing the spirit of practicing and learning basketball. This research method uses quantitative descriptives that use the target population with total sampling technique, and uses the subject of parents of basketball club participants. Collecting data using a questionnaire, the instrument of preparation is done by compiling the details of the question, data analysis by processing the questionnaire that has been filled out by the respondent, with descriptive analysis and a Likert scale. The results of the study show that parents prioritize their children's needs by 62% and their children's desires by 46%, therefore the motivation of parents to include their children so that children become healthy and fit, to meet the needs of their children, and children are not lazy to exercise. and parents also want children to make new friends/relations, and also children become basketball athletes